2SPD-038 Bevacizumab versus ranibizumab in ophthalmology outpatient surgery. (14th March 2021) - Silva, M; Morgado, M; Fonseca, O
Abstract : Background and importance: Bevacizumab has an off-label indication for the treatment of neovascular age related macular degeneration, as well as loss of vision due to diabetic macular oedema, proliferative diabetic retinopathy and loss of vision due to macular oedema secondary to retinal vein occlusion. Despite the emergence of a new therapeutic alternative, ranibizumab, for the same therapeutic indications and in an approved formulation for intravitreal administration, bevacizumab continues to be widely used in most hospitals. This is mainly due to economic criteria in the selection and acquisition purchase of medicines. Aim and objectives: Since the Centro Hospitalar Universitário Cova da Beira (CHUCB) introduced in September 2019 ranibizumab for cases refractory to treatment with bevacizumab, we decided to investigate the impact on patients treated for these pathologies as well as the economic impact resulting from this change. Material and methods: A 1 year study was carried out between October 2019 and September 2020, including patients treated with bevacizumab and ranibizumab for ophthalmic use at the CHUCB. Bevacizumab is available as a concentrate for solution for infusion (100 mg/4 mL), so the preparation of syringes containing the recommended dose of 2 mg/0.08 mL is performed in the pharmaceutical services on the day of administration, under controlled and validated aseptic conditions. Ranibizumab is available in an intravitreal syringe, so there is no manipulation by the pharmaceutical services. Results: In a total of 83 treated patients, 25 were treated with ranibizumab, after previous therapeutic failure of bevacizumab, corresponding to 30% of therapeutic failures. A total of 343 treatments were carried out with bevacizumab, which corresponded to an average value of 27.81€ per treatment, and 148 treatments with ranibizumab, which corresponded to an average value of 585.43€ per treatment. Patients currently treated with bevacizumab lost therapeutic response after, on average, nine treatments, after which the therapeutic switch was made. Conclusion and relevance: With a therapeutic success rate of around 70%, we conclude that there is therapeutic efficacy that supports the application of economic criteria in the selection of bevacizumab as the firstline treatment for the ophthalmic pathologies under study. Therefore, ranibizumab may be used as a secondline treatment, without compromising the effectiveness and safety of the treatment. References and/or acknowledgements: Conflict of interest: No conflict of interest